Теоретичні і методичні підходи до визначення поняття "фінансовий результат" у фінансовому обліку та аудиті - Мардус, Наталія Юріївна; Брік, Світлана Володимирівна (My University, 2021)
У статті обґрунтовано понятійний апарат "фінансовий результат" із позиції формування основних теоретико-методичних підходів до визначення фінансових результатів підприємства у фінансовому обліку й аудиті, що є вагомим під час вирішення питань формування фінансових результатів, що притаманно фінансовому обліку та аудиту, і надає можливість отримання найбільшого ефекту від обліково-аналітичного забезпечення, яке полягає в оперативному обліку і контролі витрат і доходів підприємства за певний період. Результати дослідження наукових підходів до визначення сутності фінансових результатів в обліковому аспекті показали, що з погляду розуміння сутності фінансового результату у фінансовому обліку й аудиті можна визначити, як процес його обчислення, який базується на правовій і нормативній базі, підпорядковується принципам нарахування фінансових результатів. Установлено, що фінансовий результат доцільно розглядати як об’єкт i інструмент, що базується на принципах відповідності витрат доходам і є основним показником в управлінні господарською діяльністю підприємства.

The article substantiates the conceptual apparatus "financial result" from the standpoint of forming the main theoretical and methodological approaches to determining the financial results of the enterprise in financial accounting and auditing, which is important in addressing the formation of financial results, which is inherent in financial accounting and auditing from accounting and analytical support, which consists in the operational accounting and control of costs and revenues of the enterprise for a certain period. The results of research of scientific approaches to determining the essence of financial results in accounting have shown that in terms of understanding the essence of financial results in financial accounting and auditing can be defined as a process of calculating it based on legal and regulatory framework and subject to accrual principles. It is established that the financial result should be considered as an object and instrument based on the principles of compliance of costs with income and is the main indicator in the management of economic activity of the enterprise. According to the results of the analysis, it can be stated that the process of accounting and analytical support of the financial results of the enterprise is based on a certain mechanism, which is characterized by the relevant elements of management. The main element of management is the legal framework and regulations on the activities of the enterprise in modern business conditions, the formation of financial results and the distribution of profits. External mechanism for regulating the formation of financial results and the use of enterprise profits and processes that affect the state of market development, industry, investment processes in the industry to which the company belongs and more. The internal mechanism of the management structure of the enterprise and the system of organization of accounting and auditing at the enterprise in relation to the formation of financial results and the use of enterprise profits. Methodical approaches, methods and procedures for internal control at the enterprise in order to manage the process of formation of financial results and manage the profitability of the enterprise.
Theoretical and methodological approaches to the definition of the term "financial result" in financial accounting and audit
Keywords: витрати; прибуток; економіка; грошові кошти; господарська діяльність підприємств; financial result; income; expenses; profit; financial accounting; audit